Sifat Organoleptik Nugget Ikan Ekor Kuning (Caesionidae) dengan Substitusi Tepung Daun Kelor (Moringa Oleifera) - Rosita Antariksawati; Anna Sarmpumpwain; Ariska Ratu Bulqis (HB PRESS, 2023)
Background: nuget was an example of a product made from ground beef and printed in the form of rectangular pieces. Then, these pieces were coated with seasoned flour. Tuna fish also contains minerals (calcium, phosphorus, iron, sodium), vitamin a (retinol), and vitamin b. 17. 3 mg of vitamin c. Purposes : knowing the making of yellow tail fish nuggets with moringa leaf flour substitution on organoleptic properties (color, aroma, taste, and texture). Methods: this researched was a quasi-experimental researched with a one-shot case studied design, used 3 nugget formulas with each comparison formula f1 2 grams: 30 grams f2 4 grams: 30 grams f3 6 grams: 30 grams. Results: the results of the statistical test used the kruskal wallis test because the data obtained were not normally distributed and the results obtained were that the three treatment variations there were no differences in color, aroma, taste, and color texture (?> 0. 05). Conclusion: the conclusion in this studied was that there was no difference in the leveled of preference (color, aroma, taste, texture) of the panelists on the organoleptic properties of color nuggets (?= 0. 068), aroma (?= 0. 071), taste (?= 0. 086), texture (?= 0. 053).